Distribution of anoectochilus roxburghii (wall.) Lindl in bach ma national park of central Vietnam (Bangladesh Journal of Botany, 2025)
Anoectochilus roxburghii is an endangered medicinal plant with high economic value in Vietnam, but its population is decreasing due to overexploitation and unfavourable conditions. The base line distribution survey of A. roxburghii in Bach Ma National Park (BMNP) was carried out for the first time in this study. Survey lines were established through interviews to develop field surveys and collect ecological characteristics. Results showed that the interview method was effective for generating potential lines. In the 9 survey lines out of 20, A. roxburghii was found to be represented by 123 individuals in the core of BMNP. Standard plots 05 and 27 were found to have the greatest ecological differences. This species was observed mainly distributed on mountain sides of evergreen and semi-deciduous natural broadleaf wood forests, where the altitude was 300 - 400 m, high humidity and large canopy. Besides, they were groups of 4-15 individuals and could produce flowers and fruits in some standard plots.Bangladesh J. Bot. 54(2): 253-260, 2025 (June)